2022
DOI: 10.1002/cbic.202200044
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Supramolecular Host for D‐(−)‐Ribose: Ratiometric Fluorescence Response via Multivalent Lectin‐Carbohydrate Interactions

Abstract: Easily synthesizable, carbazole-based organic nanoaggregates have been designed for selective detection of D-(À )-ribose at physiological pH. The addition of D-ribose results in a ratiometric change in fluorescence color from green to cyan (LOD: ~12 μM). The mechanistic studies indicate the presence of multipoint noncovalent interactions, such as hydrogen bonding and CH•••π interactions between D-ribose and acyl hydrazone and terminal pyridyl units of the probe molecule. However, such multipoint interactions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Interaction of rhodamine-based sensors with metal ions can occur either through ion-induced spirolactam ring opening or ion catalyzed hydrolysis reaction. 26 The EDTA-mediated recovery experiment with both Hg 2+ and Cu 2+ clearly indicated that the observed optical changes were due to the reversible spirolactam ring opening, and not due to ion-induced hydrolysis (Fig. 3b).…”
Section: Resultsmentioning
confidence: 81%
“…Interaction of rhodamine-based sensors with metal ions can occur either through ion-induced spirolactam ring opening or ion catalyzed hydrolysis reaction. 26 The EDTA-mediated recovery experiment with both Hg 2+ and Cu 2+ clearly indicated that the observed optical changes were due to the reversible spirolactam ring opening, and not due to ion-induced hydrolysis (Fig. 3b).…”
Section: Resultsmentioning
confidence: 81%
“…Now, we have constructed binary logic functions with Zn 2+ and Cu 2+ as dual stimulating inputs and absorbance and fluorescence as outputs (Figure 6). 75,76 Upon the addition of Zn 2+ ions (Input-1), a new fluorescence band appeared at 527 nm, attributed to a typical exciplex formation as described above. On the contrary, in the presence of Cu 2+ ions (Input-2), the emission band at 565 nm was quenched, probably due to the combined effect of PET and intramolecular charge transfer.…”
Section: Spectroscopic Studies 311 Uv−visible Studiesmentioning
confidence: 72%
“…Now, we have constructed binary logic functions with Zn 2+ and Cu 2+ as dual stimulating inputs and absorbance and fluorescence as outputs (Figure ). , …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we explored the application of compound 1 for the determination of intracellular temperature using HeLa cells as a model system. , For this, the first cytotoxicity of the compound was assayed (Figure b). More than 75% were found to be viable even when the cells were treated with ∼50 μM of compound 1 for more than 48 h. This observation indicates that the fluorogenic probe is biocompatible and therefore can be utilized for the determination of temperature inside a living mammalian cell.…”
Section: Resultsmentioning
confidence: 99%